Development and Validation of a Multidimensional Mathematical Beliefs Scale for Elementary School Students - Aras, Irianto; Darmayasa, Jero Budi (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2025)
This study aims to develop and validate a multidimensional mathematical beliefs scale for elementary school students. The instrument was developed based on Eynde, Corte, and Verschaffel’s (2002) four-dimensional framework: beliefs about teacher, beliefs about competence and significance of mathematics, mathematical beliefs as social activity, and mathematical beliefs as a domain of excellence. The development procedure followed the Mardapi model. Content validity was assessed by five expert validators using CVI, and a limited trial was conducted on 25 sixth-grade students of SDN 138 Bungi, Pinrang Regency. Data were analyzed using SPSS and Winsteps. The content validity results showed an average CVI of 0.96 (highly valid). The limited trial produced 37 valid items out of 44 (r > 0.396, p < 0.05), with high reliability (Cronbach’s Alpha = 0.886). The final instrument consists of 37 items covering four dimensions. This scale can be used to diagnose students’ mathematical beliefs profiles for designing appropriate learning interventions..